2018
DOI: 10.1016/j.aap.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of lane width and roadside configurations on speed, lateral position and likelihood of comfortable overtaking in exclusive motorcycle lane

Abstract: Construction of exclusive motorcycle lanes is one of the measures to reduce motorcycle fatalities. Previous studies highlighted the risk of crashes with roadside objects and the tendency of motorcyclists to ride with excessive speed on exclusive motorcycle lanes. However, the risk of same-direction crashes on exclusive motorcycle lanes was not explored in much detail, especially on the impact of lane geometry and roadside configurations. This study used naturalistic riding data to determine the effects of lane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…e elements within road geometry that will be investigated are horizontal curvature, lane width, and shoulder width. ese elements affect the motorcyclists' behavior, as the distance to an upcoming horizontal curve has a significant impact on the change of throttle and the brake force applied by the motorcyclist [19], and the lane width and adjacent roadside affect overtaking speed and lateral positioning [20].…”
Section: Introductionmentioning
confidence: 99%
“…e elements within road geometry that will be investigated are horizontal curvature, lane width, and shoulder width. ese elements affect the motorcyclists' behavior, as the distance to an upcoming horizontal curve has a significant impact on the change of throttle and the brake force applied by the motorcyclist [19], and the lane width and adjacent roadside affect overtaking speed and lateral positioning [20].…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that lateral separation was an important factor which might cause changes of satisfaction levels for the group of cyclists. In fact, many previous studies have indicated that lane width [33] and traffic volume [34] significantly affect the lateral position of vehicles and bicycles in mixed lanes. In our study, we also found that lateral separation between two transport modes was closer In addition, we could not ascertain whether the self-reported data by the participants in the survey was true or not [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies examined the records of fatally injured motorcyclists and collected information associated with age, sex, death cause, and time of death relative to the time of the crash. Toxicology analysis and blood alcohol concentration (BAC) results were obtained and examined, determining illegal driving behaviour as a cause of motorcycle KSI crashes and modelling crash severity by considering the risk indicators of drivers and roadways for reducing the severity of crashes and enhancing the safety performance of the traffic system [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Taxonomymentioning
confidence: 99%